2022
DOI: 10.1029/2022gl099292
|View full text |Cite
|
Sign up to set email alerts
|

Locating the Precise Sources of High‐Frequency Microseisms Using Distributed Acoustic Sensing

Abstract: A fiber-optic cable on the seafloor is used to locate the sources of high-frequency microseisms with an unprecedented precision • The sources of high-frequency microseisms quickly move within narrow areas of a few kilometers • The constantly changing source locations are most likely related to the ephemeral behaviors of wind Supporting Information:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Beyond the Ios fault line at roughly 25 km, the Scholte waves are no longer present in the data. A previous submarine DAS study with a similar setup showed a gradual change in the frequency content of microseismic sources with increasing depth (Xiao et al, 2022).…”
Section: Secondary Microseisms and Scholte Wavesmentioning
confidence: 73%
“…Beyond the Ios fault line at roughly 25 km, the Scholte waves are no longer present in the data. A previous submarine DAS study with a similar setup showed a gradual change in the frequency content of microseismic sources with increasing depth (Xiao et al, 2022).…”
Section: Secondary Microseisms and Scholte Wavesmentioning
confidence: 73%
“…Spica, Nishida, et al, 2020;Z. J. Spica -7-non-peer reviewed preprint submitted to EarthArXiv and Seismological Research Letters et al, 2022;Cheng et al, 2021;Williams et al, 2021;, assess detailed 200 nonlinear ground motion amplification , or precisely locate the sources 201 of microseisms (Xiao et al, 2022).…”
Section: Overview Of the Current Fields Of Application In Earth Sciencesmentioning
confidence: 99%
“…They occupy the lower end of the oceanic wave spectrum, with a dominant frequency typically between 0.005 and 0.05 Hz (Herbers et al, 1994(Herbers et al, , 1995, and are primarily generated by nonlinear interactions between higher-frequency wind waves (Hasselmann et al, 1963;Longuet-Higgins & Stewart, 1962). Wind waves and ocean swells have shorter periods, typically ranging from 0.04 to 1 Hz, and are the dominating signal in subsea DAS studies (Lindsey et al, 2019;Williams et al, 2019;Xiao et al, 2022). Besides, the typical frequency band of tsunamis ranges from about 0.14 to 5 mHz (200-7,140 s).…”
Section: Introductionmentioning
confidence: 99%
“…DAS utilizes the optical phase changes in Rayleigh backscattered light within an optical fiber to function as thousands of vibration sensors. This innovative approach enables the fiber to act as a dense array capable of continuously detecting and analyzing seismo-acoustic signals along tens of kilometers (Farghal et al, 2022;Lindsey et al, 2019;Lior et al, 2021;Romanowicz et al, 2023;Sladen et al, 2019;Spica et al, 2020Spica et al, , 2022Spica et al, , 2023Viens et al, 2023;Williams et al, 2019;Xiao et al, 2022;Yang et al, 2022;Zhan, 2019). Unlike traditional sensors, DAS provides high-resolution data over large distances, allowing for real-time monitoring of seismic and ocean waves with unprecedented coverage.…”
Section: Introductionmentioning
confidence: 99%